Kontribusi Penerjemahan Terhadap Branding Global Pariwisata Indonesia: Perspektif Tujuan Pembangunan Berkelanjutan - misnah mannahali; Femmy Angreany; Alamsyah Alamsyah; Arlian Fachrul Syaputra (TALENTA, 2026)
Tourism is one of Indonesia’s leading sectors in fostering economic growth and supporting the achievement of the Sustainable Development Goals (SDGs). In this context, translation plays a crucial role not only as a means of communication but also as a strategic instrument in building Indonesia’s global tourism branding. This study employs a descriptive qualitative approach through content analysis of official tourism promotion documents, such as the Wonderful Indonesia website, multilingual brochures, and digital materials, linked to national policies on sustainable tourism. The findings indicate that translation significantly contributes to strengthening Indonesia’s image in the international market, enhancing accessibility and inclusivity for international tourists, and reinforcing cultural diplomacy. However, several challenges remain, including inconsistent translation quality, limited professional resources, and adaptation to digital transformation. Therefore, improving translation professionalism and fostering cross-sector collaboration are essential to strengthen Indonesia’s tourism branding while supporting the achievement of the SDGs.